Intervensi Kemanusiaan dan Jatuhnya Kuasa Kolonel Muammar Gaddafi di Libya - Jerry Indrawan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
This article explains on civil war and the humanitarian intervention in Libya, in which it was taken over by NATO coalition forces through the Operation Unified Protector. The fighting in Libya ended in late October 2011 following the death of Muammar Gaddafi. Officially NATO announced that it would suspend its military operations in Libya on October 31, 2011, but the new Libyan government (NTC) requested NATO's mission in the country to be extended until the end of 2011. On 27 October, the UN Security Council voted to end its mandate NATO military forces in Libya on October 30, 2011. The implications of NATO military operations in Libya have side effects and unintended consequences. So far, armed conflicts in Libya are still going on following the death of Gaddafi several years ago.